Quantification of thrombin activatable fibrinolysis inhibitor (TAFI) gene polymorphism effects on plasma levels of TAFI measured with assays insensitive to isoform-dependent artefact - Frère, Corinne; Emmanuel Morange, Pierre; Saut, Noémie; Tregouet, David Alexandre; Grosley, Mariana; Beltran, Jérôme; Juhan-Vague, Irène; Alessi, Marie-Christine (Thrombosis and Haemostasis, 2005)
Reports have reappraised the genotype-dependent variation of Thrombin Activatable Fibrinolysis Inhibitor (TAFI), demonstrating that, in some enzyme-linked immunosorbent assays (ELISA), decreased antibody reactivity towards the TAFI 325 Ile isoform led to erroneous TAFI levels. Assays free of this artefact are required to evaluate the contribution of theTAFI gene polymorphisms toTAFI level variability.TAFI levels were measured in 209 individuals with both immunological and functional assays. Each assay was characterized, in particular for its reactivity towards the 325 Thr and Ile isoforms. Two ELISAs were found to have a lower reactivity towards the Ile isoform, leading to an overesti-mate of the magnitude of variation between two different genotypes. In contrast, one ELISA, as well as functional assays, was found to be free of genotype-dependent artefact constituting a reliable method to detect true quantitative variations of TAFI levels. Using these reliable methods, univariate and haplotype analyses revealed that TAFI gene polymorphisms explain 25% of TAFI level variability. This effect seems to be the consequence of the joint independent action of two polymorphisms, one in the 5’ (G-1102T) and the other in the 3’ region (T+1583A) of the TAFI gene.
Keywords: TAFI; monoclonal antibody; ELISA; genotype; polymorphism